Curse or Blessing? Obesity and Income-Related Inequality in the Chinese Labor Force - Tang, Chengxiang; Yang, Xiaocong; Peng, Fei; Hu, Xianglian (Frontiers in Public Health, 2021)
China owns a huge labor force of around half billion workers in 2018. However, little is known about the prevalence of obesity and the association between obesity and economic status in this special population. By employing the concentration index (CI) and decomposition analysis, this paper addresses this knowledge gap by using the most recent nationally representative dataset. In specific, this study examines the prevalence of obesity and the socioeconomic gradient in the probability of obesity among Chinese workers between 16 and 65. Our results show that the prevalence of obesity is completely different by using a different measure: the overall prevalence of being general obesity (measured by body mass index, BMI ≥ 28) varies by gender and residency from a minimum of 5.88% to a maximum of 9.46%, whereas abdominal obesity (measured by waist circumference, WCmale ≥ 85 cm & WCfemale ≥ 80 cm) prevalence presents a socking level from 64.53% to 67.69%. Moreover, the results show a pro-rich distribution of obesity (general and abdominal) among male workers (CIBMI = 0.112; CIWC = 0.057) and a pro-poor distribution among female workers (CIBMI = −0.141; CIWC = −0.166). We also find that the direction of the contribution of socioeconomic factors to income-related inequalities in obesity differs by gender. These results have substantial implications for the measurement of socioeconomic inequality in adiposity and for improving health-related policies targeting the Chinese labor force.